WRKY45 is a negative regulator of Botrytis cinerea resistance through the JA/ET signaling pathway in Arabidopsis - Ran, Huifang; Yuan, Zunyi; Chen, Zhihao; Mao, Yongxin; Bao, Shiwei; Chen, Yuyu; Chen, Mo; Zhang, Haiyan; Gong, Wenfeng (Frontiers in Plant Science, 2025)
Botrytis cinerea is a necrotrophic fungal pathogen that causes significant crop damage, yet the molecular mechanisms underlying plant defense remain incompletely understood. Here, we identify WRKY45 as a negative regulator of Arabidopsis resistance to B. cinerea through the suppression of JA/ET-mediated defense signaling. Our results show that WRKY45 expression was induced by B. cinerea infection, peaking 48 hours post-inoculation. Loss of WRKY45 function enhanced resistance, while WRKY45 overexpression increased susceptibility and cellular damage, as indicated by elevated electrolyte leakage, higher malondialdehyde levels, and reduced chlorophyll content. RNA-seq analysis identified 1,850 differentially expressed genes in wrky45 mutants, with strong enrichment of JA/ET-responsive pathways. Defense-related genes, including ORA59, PDF1.2, ERF104, and ERF1, were markedly upregulated in wrky45 but suppressed in overexpression lines, as confirmed by qRT-PCR. Electrophoretic mobility shift assays and dual-luciferase assays demonstrated that WRKY45 directly binds to the ORA59 promoter inhibiting its transcription, and represses the expression of PDF1.2, ERF104, and ERF1. Together, these results show that WRKY45 functions as a negative regulator by suppressing the expression of JA/ET-mediated defense genes, thereby modulating plant resistance to B. cinerea.